1974
DOI: 10.1901/jeab.1974.21-519
|View full text |Cite
|
Sign up to set email alerts
|

A DETAILED ANALYSIS OF THE EFFECTS OF d‐AMPHETAMINE ON BEHAVIOR UNDER FIXED‐INTERVAL SCHEDULES1

Abstract: Pigeons were exposed to fixed-interval schedules of food reinforcement with durations of 300 sec, 100 sec, or 40 sec. A range of doses of d-amphetamine vas administered to each pigeon, and the resulting behavior was analyzed at several levels of detail. Average rates in different portions of the intervals predicted the magnitude of the drug's effect, but a finer analysis showed that average rates did not adequately characterize the behavior in some parts of the intervals. The probability of responding in diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
72
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 15 publications
9
72
0
Order By: Relevance
“…A similar analysis was performed on the wide range of both overall and running response rates obtained over the different FR parameter values (Figure 11). An analysis of run rates was included to compare effects of ethanol on the relatively homogeneous response rates that occur under FR schedules when pauise duration is excluded, thereby circumventing a potential p)roblem in averaging different rates under Fl schedules (Branch & Gollub, 1974). As witlh the local rates under the Fl schedule, there was a general tendency for the lowest FR rates, obtained at the higher FR values, to be increased at doses that decreased the higher FR rates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar analysis was performed on the wide range of both overall and running response rates obtained over the different FR parameter values (Figure 11). An analysis of run rates was included to compare effects of ethanol on the relatively homogeneous response rates that occur under FR schedules when pauise duration is excluded, thereby circumventing a potential p)roblem in averaging different rates under Fl schedules (Branch & Gollub, 1974). As witlh the local rates under the Fl schedule, there was a general tendency for the lowest FR rates, obtained at the higher FR values, to be increased at doses that decreased the higher FR rates.…”
Section: Resultsmentioning
confidence: 99%
“…The use of average local response rates has been criticized because the average rate derived from cumulating responses into segments of the interval potentially results in the combination of different rates; under such conditions the average figure may not accurately reflect the measures on which it is based (Branch & Gollub, 1974 (Barrett, 1977; also see review by McKearney, 1979, and articles by Poling & Appel, 1978;Urbain, Poling, Millam, & Thompson, 1978). In addition, the actual consequences of responding in the presence of a drug may modify the subsequent effects of that drug on behavior (Smith & McKearney, 1977 a month, during which time behavior was stabilized.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluations of patterning based on data grouped over multiple intervals typically have been misleading about the nature of behavior as it occurs in individual intervals. Branch and Gollub (1974) showed that the averaged data need not correspond with behavior occurring in any individual interval.The peak procedure can show the sensitivity of animals to time both before and after the fixed interval has elapsed, because it involves interpolated trials uninterrupted by food delivery. What is missing is information about behavior on each empty trial.…”
mentioning
confidence: 99%
“…Break-and-run patterns (Cumming & Schoenfeld, 1958;Schneider, 1969), on the other hand, are typified by an abrupt transition from little or no responding to a high and relatively constant response rate. Whether this type of pattern is actually distinct from scalloping has been called into question by subsequent analysts (Branch & Gollub, 1974;Dews, 1979;Lowe & Harzem, 1977). The oscillatory, "pause-respond" pattern characteristic of animal performance-whether it be of the scalloping or break-and-run varieties-is often considered indicative of sensitivity to the temporal structure of the FL contingency.…”
mentioning
confidence: 99%